Tribological properties of metallic nanoparticles as lubricant additives under the applied electric currents. Issue 9 (16th October 2018) - Si, Lina; Pan, Yan; Zhang, Xiaoqing; Wang, Jie; Yao, Jia; Wang, Yanjie; Liu, Fengbin; He, Feng
Abstract : Purpose: This paper aims to clarify the effects of metallic nanoparticles (NPs) additives and room temperature ionic liquids (ILs) on the tribological performance of electric contacts. Design/methodology/approach: Tribological properties of copper (Cu) and silver (Ag) NPs as lubricant additives in different lubricants of ILs or polyalphaolefin (PAO) oils under applied electric currents were investigated. After tribological tests, morphologies of worn surfaces were observed; meanwhile, lubrication and anti-wear properties were analyzed. Findings: The mixture solution of the IL and Cu NPs showed desirable lubrication and anti-wear properties due to the reduction of electrocorrosion and the enhancement of rolling effects of particles in the contact region. The anti-wear performance of Cu NPs is better than that of Ag NPs due to the difference in the particle size. The PAO oil with the Cu NPs additives showed poor lubrication properties due to the low solubility of the particles in the oil. When the direction of applied current was changed, the friction of the lubricant with better conductivity was more stable in the variation trend. Originality/value: This paper begins with a study of tribological properties of Cu and Ag NPs as lubricant additives in different lubricants of IL or PAO oils under applied electric currents. The authors then propose several methods and possible solutions which could be implemented to improve the tribological performance of electric contacts.